PESONA PERINGATAN MAULID NABI DI MATA SANTRI MILENIAL DAN GEN Z - Mujlauwidzatul Husna; Nikmatul Azizah; Ita Ma’rifatul Fauziyah (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2025)
The Prophet’s Maulid is celebrated annually by Muslims across generations. One unique example is how a boarding school in Yogyakarta celebrates the Maulid with participation from various groups. This study aims to understand how commemorating the Prophet's Maulid contributes to the formation of religious identity among Millennial and Gen Z students at Al Barokah Islamic Boarding School in Yogyakarta. The research approach used is mixed, this research combines quantitative and qualitative methods. The quantitative method is in the form of a survey of 50 students to measure the level of understanding and participation in Prophet's Maulid activities, and their influence on strengthening religious values. Meanwhile, the qualitative method took the form of in-depth interviews with 5 students and religious leaders to explore the deeper meaning of their personal experiences and perceptions of the celebration of the Prophet's Maulid. The results showed that the celebration of the Prophet's Maulid has a role in shaping the religious identity of students who are millennials and Gen Z, especially in terms of (1) strengthening the value of faith in the form of faith in prophets and rosul; (2) good behavior, namely charity in the form of material, time, energy and thoughts; and (3) social values in the form of da'wah through social media. This study highlights how Islamic boarding school shape students’ religious identity, both for themselves and in their engagement with local and digital communities.